A crítica ensaística de Osman Lins sobre o acesso do jovem escolar à cultura brasileira - Ferreira, Eliane Aparecida Galvão Ribeiro [UNESP]; Bulhões, Ricardo Magalhães (My University, 2014)
This text aims to address the critical essays of Osman Lins on the corpus of his works, reading and study, which consists of Portuguese textbooks adopted in schools for the teaching of the national language in the Secondary Course. More specifically, we intend to reflect on how Osman Lins analyzes the procedures adopted by the authors of these textbooks to introduce learners into Brazilian literature. Our object of study and analysis is restricted to six trials Lins published originally in 1965, the newspaper of Pernambuco University Press and later, in 1977, were collected in the form of the first chapter, titled "The Book didactic - First time: 1965 " (1977, p.13-40), the book From the Dream and Glory: Brazilian uncultural problems.

Este texto tem por objetivo tratar da crítica ensaística de Osman Lins sobre o corpus de obras, para leitura e estudo, que compõe os compêndios de Português adotados nas escolas para o ensino da língua nacional no Curso Secundário. Mais especificamente, pretende-se refletir sobre como Osman Lins analisa os procedimentos adotados pelos autores desses compêndios para apresentar aos educandos a literatura brasileira. Nosso objeto de estudo e análise restringe-se a seis ensaios que Lins publicou, originalmente, no ano 1965, no jornal Imprensa Universitária de Pernambuco e, posteriormente, em 1977, que foram recolhidos sob a forma de primeiro capítulo intitulado “O livro did|tico – primeiro tempo: 1965” do livro Do ideal e da glória: problemas inculturais brasileiros.
Keywords: Literatura e crítica literária; Crítica ensaística; Osman Lins